Perkembangan Kognitif Anak Usia Dini Melalui Pembelajaran Berbasis Lingkungan - Nur Rahma Azlinda; Sri Jumiaty Permatasari (Jurnal E-MAS (Edukasi dan Pembelajaran Anak Usia Dini), 2026)
Early childhood cognitive development is a crucial aspect in shaping children’s ability to think, understand, and solve problems. One effective approach to support this development is environment-based learning. This study aims to review various literature sources regarding the role of the environment as a learning medium in enhancing early childhood cognitive abilities. The method used is a qualitative literature review by analyzing scientific journals, books, and relevant previous studies. This review focuses on synthesizing theoretical and empirical findings on the contribution of environment-based learning to early childhood cognitive development. The findings indicate that both natural and social environments provide direct learning experiences that stimulate children’s curiosity, improve observation skills, and strengthen critical and creative thinking. Environment-based learning also enables children to learn in a contextual manner, making concepts easier to understand and remember. In addition, interaction with the environment supports language development, classification skills, and simple problem-solving abilities. Teachers play an important role in designing and facilitating learning activities that effectively utilize the surrounding environment in accordance with children’s developmental stages. The success of this approach largely depends on teachers’ ability to create meaningful and developmentally appropriate learning experiences. Thus, environment-based learning is an effective strategy for promoting holistic cognitive development in early childhood. The implication of this study suggests that integrating environmental contexts into learning activities should be systematically implemented in early childhood education to optimize cognitive stimulation through experiential learning.